Preclinical and first-in-human of purinostat mesylate, a novel selective HDAC I/IIb inhibitor, in relapsed/refractory multiple myeloma and lymphoma - Linyu Yang; Qiang Qiu; Jie Wang; Yi Wen; He Li; Rui Liang; Yunyu Feng; Fang Wang; Xiaojing Lin; Minghai Tang; Jianhong Yang; Heying Pei; et al. (Signal Transduction and Targeted Therapy)
Abstract Simultaneously targeting key pathogenic drivers and remodeling of the tumor microenvironment represents a critical therapeutic strategy for relapsed or refractory (r/r) multiple myeloma (MM) and lymphoma. Purinostat mesylate (PM), a highly selective HDAC I/II binhibitor, exhibits excellent antitumor activity in MM and lymphoma cell lines and mouse models, outperforming the pan-HDAC inhibitor panobinostat or first-line/second-line multi-drug combinations. Different from panobinostat, bulk RNA-seq analysis revealed that PM suppressed essential tumor survival factors and triggered inflammation and interferon responses. The scRNA-seq of 5TMM models further indicated that PM enhanced antitumor immunity by boosting monocyte- and T cell-mediated immune responses. In a phase I trial (NCT05526313; N = 29) of PM at doses up to 15 mg/m², treatment-related Grade ≥3 adverse events predominantly comprised hematologic toxicities: thrombocytopenia (75.9%), neutropenia (55.2%), leukopenia (41.4%), and lymphopenia (31.0%), with no dose-limiting toxicities observed. PM monotherapy achieved a disease control rate of 72.7% (8/11) and an objective response rate (ORR) of 9.1% (1/11) in r/r MM. Notably, r/r lymphoma patients showed an ORR of 61.6% (11/18), particularly reaching 63.6% (7/11) with 6 complete responses in diffuse large B-cell lymphoma (DLBCL). Treatment responders exhibited enhanced immune activation, with elevated CD3+CD8+ T cells and increased cytokine levels, such as IFN-γ and CXCL10. Overall, PM is safe and moderately effective in MM, but highly effective in lymphoma. Additionally, PM combined with pomalidomide and dexamethasone showed strong synergistic activity in r/r MM treatment. These findings support further open-label, multicenter phase Ib/IIa trials of PM combination therapy with immunomodulators for r/r MM, as well as phase II monotherapy trials for r/r DLBCL and r/r T-cell lymphoma.